Proposta de um protótipo que realize medição não-invasiva de energia elétrica para o campus da UFERSA-Mossoró - Guimarães, Jerffeson da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The application of telecommunications and automation technologies in electric power grids, which defines the Smart Grid, provide energy efficiency for both concessionaires and final consumers. The present work aims to demonstrate the necessary materials and electrical connections for a future construction of a prototype that can realize a non-invasive electric energy reading on the electric meter installed in UFERSA - Mossoró campus - east side. The necessary materials are: a microcontroller, which receives the data sent from the electronic meter CRONOS 7023, using an infrared sensor and then transmitting the data using the Wireless SD shield to a mobile application, in which it will present in the interface the data desired by the future designer.
Monografia
Keywords: Arduino; Smart Grid; Medição inteligente; Sensor infravermelho; Eficiência energética; Arduino; Energy Efficiency; Infrared sensor; Smart Grid; Intelligent measurement; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA